1989
DOI: 10.1104/pp.90.1.180
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Root Tumorigenesis Assay to Detect Genotypic Variation in Susceptibility of Thirty-four Cultivars of Pisum sativum to Crown Gall

Abstract: We developed a quantitative assay to measure tumorigenesis on roots and root crowns, the natural sites of Agrobacterium tumefaciens infection. Efficiency of tumor formation and tumor weight on seedlings of Pisum sativum 'Little Marvel' were directly proportional to the logarithm of inoculum concentration. Depth of wounding prior to inoculation also significantly influenced tumor weight but not efficiency. Mean weight of tumors that developed in response to inoculation with strain B6 varied significantly among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

1989
1989
2001
2001

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Three of the lines-P1272185, B586-105(l), and B786-287( 1)-developed unusually large tumors (more than 9 mm in diameter), and this 'supersusceptible' phenotype was transmitted to Fl and F2 progeny from selfed parents. Tumor response phenotypes were also compared with those of 34 commercial cultivars whose responses were documented in a previous study (4). Tumors on the three supersusceptible lines (for example, Fig.…”
Section: Supersusceptibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Three of the lines-P1272185, B586-105(l), and B786-287( 1)-developed unusually large tumors (more than 9 mm in diameter), and this 'supersusceptible' phenotype was transmitted to Fl and F2 progeny from selfed parents. Tumor response phenotypes were also compared with those of 34 commercial cultivars whose responses were documented in a previous study (4). Tumors on the three supersusceptible lines (for example, Fig.…”
Section: Supersusceptibilitymentioning
confidence: 99%
“…4,8,15,18), studies on inheritance have been limited to grapevine (12,20). We recently developed an assay that results in a 95 to 100% infection frequency on susceptible pea cultivars and used it to demonstrate the occurrence of quantitative variation in susceptibility of 34 cultivars (4). The objectives of the current study were to identify variation in responses of more than 1300 pea genotypes.…”
mentioning
confidence: 99%
“…Roots were immersed for 5 min in inoculum at different concentrations and then were planted in growth pouches. Infection was rated after 2 weeks by the percentage of inoculation sites that developed tumors (17). Soil Mutants that exhibited wild-type virulence in the growth pouch assay were selected for studies of behavior in soil and in sand (Table 2).…”
mentioning
confidence: 99%
“…A growth pouch assay was used to measure virulence of mutants in vitro (17). Seedlings with root lengths of 10 to 20 cm were wounded at two sites:…”
mentioning
confidence: 99%
“…Various assays have been used to study tumor formation and to determine the relative virulence of mutant strains with respect to that of the wild-type bacterium. These assays include Anand and Heberlein's potato disc assay (1), Lippincott and Heberlein's pinto bean leaf assay (4), the pea root assay described by Hawes et al (2), and a carrot root assay originally described by Klein and We found that the best way to quantitate bacterial virulence in this assay was to determine the number of bacteria needed to form tumors at 50% of the inoculated sites. Other parameters, such as tumor weight, diameter, and length of time to form tumors, were explored but were not found to give a linear response as the number of bacteria inoculated increased.…”
mentioning
confidence: 99%